Piezoelectric and dielectric characterization of corona and contact poled PZT-epoxy-MWCNT bulk composites. (7th October 2016) - Banerjee, S; Cook-Chennault, K A; Du, W; Sundar, U; Halim, H; Tang, A
Abstract: Three-phase lead zirconate titanate (PZT, PbZr0.52 Ti0.48 O3 )-epoxy-multi-walled carbon nanotube (MWCNT) bulk composites were prepared, where the volume fraction of PZT was held constant at 30%, while the volume fraction of the MWCNTs was varied from 1.0%–10%. The samples were poled using either a parallel plate contact or contactless (corona) poling technique. The piezoelectric strain coefficient ( d 33 ), dielectric constant ( ε ), and dielectric loss tangent (tan δ ) of the samples were measured at 110 Hz, and compared as a function of poling technique and volume fraction of MWCNTs. The highest values for dielectric constant and piezoelectric strain coefficients were 465.82 and 18.87 pC/N for MWCNT volume fractions of 10% and 6%, respectively. These values were obtained for samples that were poled using the corona contactless method. The impedance and dielectric spectra of the composites were recorded over a frequency range of 100 Hz–20 MHz. The impedance values observed for parallel-plate contact poled samples are higher than that of corona poled composites. The fractured surface morphology and distribution of the PZT particles and MWCNTs were observed with the aid of electron dispersion spectroscopy and a scanning electron microscope. The surface morphology of the MWCNTs was observed with the aid of a field emission transmission electron microscope.